Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Sikap Siswa tentang Abortus - Avinda Krisna Lukwinata; Ning Arti Wulandari (STIKes Patria Husada Blitar, 2014)
According to the National Commission for Child Protection in Indonesian at 2008 to 2010 abortions reached 2.5 million cases and 62.2% among teenagers. That caused by lacking of knowledge about abortion at teenagers. The impac of lacking of knowledge is bad attitude towards abortion. Method: Research design was quasy experiment. Research sample was 22 students of 1 and 2 grade SMA PGRI Srengat at April 22nd until May 5th, 2012, its choosed with total sampling. Data collected by observation using checklist. Analysis using Wilcoxon Signed Rank Test, with significant level ≤0.05. Result: The results showed that health education influence knowledge and attitude, with p value 0.001. Discussion: Health education using video and leaflet, effective to improve knowledge and attitude student about abortion.